Effectiveness of Metacognitive Therapy to Improve Verbal and Working Memories in PTSD Veterans - S. Ghorbani; H. Kazemi Zahrani (Afarand Scholarly Publishing Institute, 2015)
Aims: Memory is one of the psychological processes that plays a major role in creating and sustaining post-traumatic stress disorder. The purpose of this study was to determine the effectiveness of Metacognitive therapy on working memory and verbal memory in veterans with post-traumatic stress disorder patients. Materials & Methods: This quasi-experimental research was conducted with pretest-posttest design in all post-traumatic stress disorder patients who were referred to the consultant centers of Esfahan and Najafabad cities, Iran, in spring and summer 2014. Among these, 30 patients were selected by available sampling and were randomly divided into experimental and control groups. All patients were assessed by demographic information questionnaire, Beck Depression Inventory, Beck Anxiety Inventory, Wechsler test of verbal memory WMS-II & N-back at pretest and posttest. The experimental group received 8 metacognitive therapy sessions. Subjects in each group were tested before and after the intervention. Data were analyzed by MANCOVA in SPSS 18 software. Findings: At posttest, the experimental group showed a significant improvement in working memory and verbal memory (p<0.05). Also the experimental group did not show significant differences in the components of a simple verbal memory and second level of working memory. Conclusion: Metacognitive therapy improves the working memory and verbal memory of post-traumatic stress disorder patients.